Systems crosstalk between antiviral response and cancerous pathways via extracellular vesicles in HIV-1-associated colorectal cancer - Zimei Chen; Ke Yang; Jiayi Zhang; Shufan Ren; Hui Chen; Jiahui Guo; Yizhi Cui; Tong Wang; Min Wang (Computational and Structural Biotechnology Journal, 2023)
HIV-1 associated colorectal cancer (HA-CRC) is one of the most understudied non-AIDS-defining cancers. In this study, we analyzed the proteome of HA-CRC and the paired remote tissues (HA-RT) through data-independent acquisition mass spectrometry (MS). The quantified proteins could differentiate the HA-CRC and HA-RT groups per PCA or cluster analyses. As a background comparison, we reanalyzed the MS data of non-HIV-1 infected CRC (non-HA-CRC) published by CPTAC. According to the GSEA results, we found that HA-CRC and non-HA-CRC shared similarly over-represented KEGG pathways. Hallmark analysis suggested that terms of antiviral response were only significantly enriched in HA-CRC. The network and molecular system analysis centered the crosstalk of IFN-associated antiviral response and cancerous pathways, which was favored by significant up-regulation of ISGylated proteins as detected in the HA-CRC tissues. We further proved that defective HIV-1 reservoir cells as represented by the 8E5 cells could activate the IFN pathway in human macrophages via horizonal transfer of cell-associated HIV-1 RNA (CA-HIV RNA) carried by extracellular vesicles (EVs). In conclusion, HIV-1 reservoir cells secreted and CA-HIV RNA-containing EVs can induce IFN pathway activation in macrophages that contributes to one of the mechanistic explanations of the systems crosstalk between antiviral response and cancerous pathways in HA-CRC.